Abuse of Authority: A Meaning Deconstruction - Kurnia Dewi Anggraeny (Jurnal Hukum Novelty, 2020)
Introduction to The Problem:Â As part of the organization of the government duties and community services, the authority to make a decision is attributed to the government officials (inherent aan het bestuur), which has led many to become a suspect and a convict. On the other hand, it is believed that the government's policies are not subject to the law.Purpose/Objective Study: This study aims to determine to analyze abuse of authority according to a meaning deconstructionDesign/Methodology/Approach: The research applied normative juridical approach as the logical consequence of sui generis of law.Findings: Each network of a structure of meaning is always presented in the form of binary opposition. One of the elements is marginalized and abandoned. Similarly, in the field of law, the term "abuse of authority," which is often connected to the damage that occurs to the state's financial condition, is seen as an absolute part of the Criminal Law. Arbitrarily, it replaces the function of the State Administrative Law. The "financial loss," which is then known as corruption, is the result of 'abuse of authority,' originated from the State Administrative Law. Through Jacques Derrida's perspective, a marginalized binary opposition is made into being. It is not to dominate others, but to share the views. The disjuncture between the state administrative law and criminal law has caused an unresolved issue of corruption. Through Paul Scholten's perspective, in essence, the criminal law has abandoned the social fact that there is a strong correlation between the deeds in the state administrative law and those in the criminal law, which is in the theoretical domain of administrative criminal law. The abandonment is against the hulprecht principle related to the implementation of the law mentioned above. The research employed a normative juridical method based on secondary data using philosophical, conceptual, and legal approaches.Originality: This article discusses specifically abuse of authority, a meaning deconstruction in terms of criminal law and state administrative lawPaper Type: General Review